THE INFLUENCE OF BRAND TRUST, BRAND IMAGE, AND CELEBRITY ENDORSEMENT ON CONSUMER PURCHASE DECISION OF SCARLETT WHITENING PRODUCT - Lingkan Beatrix Wowiling; Frederik G. Worang; Shinta J. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this study is to know the simultaneous and partial influence of brand trust, brand image, and celebrity endorsement on consumer purchase decision of Scarlett Whitening product in Manado. This research used multiple regression analysis with sample of 60 respondents. Brand trust, brand image, and celebrity endorsement have a simultaneous influence on consumer purchase decision of Scarlett Whitening product in Manado. The company should focus more on the things that can grow consumer’s trust for the product like focusing on its benefits given to consumers, increase trust the products, maintaining a good image of the company, and should associate celebrities with high levels of attractiveness and popularity, and also has a good attitude.   Keywords: brand trust, brand image, celebrity endorsement, consumer purchase decision